Answer:
See explanation
Step-by-step explanation:
1. Find the GCF of 40 and 44:
![40=\underline{2\cdot 2}\cdot 2\cdot 5\\ \\44=\underline{2\cdot 2}\cdot 2\cdot 11\\ \\GCF(40,44)=2\cdot 2=4](https://tex.z-dn.net/?f=40%3D%5Cunderline%7B2%5Ccdot%202%7D%5Ccdot%202%5Ccdot%205%5C%5C%20%5C%5C44%3D%5Cunderline%7B2%5Ccdot%202%7D%5Ccdot%202%5Ccdot%2011%5C%5C%20%5C%5CGCF%2840%2C44%29%3D2%5Ccdot%202%3D4)
So,
![40+44=4\cdot 10+4\cdot 11=4\cdot (10+11)](https://tex.z-dn.net/?f=40%2B44%3D4%5Ccdot%2010%2B4%5Ccdot%2011%3D4%5Ccdot%20%2810%2B11%29)
2. Find the GCF of 13 and 52:
![13=\underline{13}\\ \\52=2\cdot 2\cdot \underline{13}\\ \\GCF(13,52)=13](https://tex.z-dn.net/?f=13%3D%5Cunderline%7B13%7D%5C%5C%20%5C%5C52%3D2%5Ccdot%202%5Ccdot%20%5Cunderline%7B13%7D%5C%5C%20%5C%5CGCF%2813%2C52%29%3D13)
So,
![13+52=13\cdot 1+13\cdot 4=13\cdot (1+4)](https://tex.z-dn.net/?f=13%2B52%3D13%5Ccdot%201%2B13%5Ccdot%204%3D13%5Ccdot%20%281%2B4%29)
3. Find the GCF of 15 and 81:
![15=\underline{3}\cdot 5\\ \\81=\underline{3}\cdot 3\cdot 3\cdot 3\\ \\GCF(15,81)=3](https://tex.z-dn.net/?f=15%3D%5Cunderline%7B3%7D%5Ccdot%205%5C%5C%20%5C%5C81%3D%5Cunderline%7B3%7D%5Ccdot%203%5Ccdot%203%5Ccdot%203%5C%5C%20%5C%5CGCF%2815%2C81%29%3D3)
So,
![15+81=3\cdot 5+3\cdot 27=3\cdot (5+27)](https://tex.z-dn.net/?f=15%2B81%3D3%5Ccdot%205%2B3%5Ccdot%2027%3D3%5Ccdot%20%285%2B27%29)
4. Find the GCF of 64 and 28:
![64=\underline{2\cdot 2}\cdot 2\cdot 2\cdot 2\cdot 2\\ \\28=\underline{2\cdot 2}\cdot 7\\ \\GCF(64,28)=2\cdot 2=4](https://tex.z-dn.net/?f=64%3D%5Cunderline%7B2%5Ccdot%202%7D%5Ccdot%202%5Ccdot%202%5Ccdot%202%5Ccdot%202%5C%5C%20%5C%5C28%3D%5Cunderline%7B2%5Ccdot%202%7D%5Ccdot%207%5C%5C%20%5C%5CGCF%2864%2C28%29%3D2%5Ccdot%202%3D4)
So,
![64+28=4\cdot 16+4\cdot 7=4\cdot (16+7)](https://tex.z-dn.net/?f=64%2B28%3D4%5Ccdot%2016%2B4%5Ccdot%207%3D4%5Ccdot%20%2816%2B7%29)
Answer:
g(x) = | x - 2 | + 10
Step-by-step explanation:
given g(x) then g(x± h ) is a horizontal translation of g(x)
• if h > 0 then a move to the left of h units
• if h < 0 then a move to the right of h units
here the move is 2 units to the right, then
g(x) = | x - 2 |
given g(x) then g(x) + c is a vertical translation of g(x)
• if c > 0 then a move up
• if c < 0 then a move down
here the move is 10 units up , then
g(x) = | x - 2 | + 10
A = (h * b) / 2
A = 200
h = 4b
200 = (b(4b) / 2
200 * 2 = b * 4b
400 = 4b^2
400 / 4 = b^2
100 = b^2
sqrt 100 = b
10 = b ..... base is 10 cm
h = 4b
h = 4(10)
h = 40 <=== height is 40 cm
Answer:
<AFB
Step-by-step explanation:
The angle that is a vertical angle with <EFD would be the angle that is vertically opposite and equal to <EFD.
Taking a look at the diagram, yiu would observe that <AFB is vertically opposite to <EFD. Therefore, <AFB is a vertical angle with <EFD.
Answer: do not know just do it
Step-by-step explanation: